THE INFLUENCE OF MINK-FEMALES` AGE OF DIFFERENT GENOTYPES OF THE SCANDINAVIAN SELECTION ON FERTILITY INDICATORS - Яремич, Н. В. (Scientific Progress & Innovations, 2014)
They conducted the research of mink-females fertility indicators with different genotypes of the Scandinavian selection which depends on duration of their usage for reproduction in a farm. It is established that the females` type indicators of reproductive ability do not depend on the colour and grow with age. So, the minks of genotypes Pearl and Scanblack the maximum indexes of fertility indicators are registered at females of 3 years usage - 6,25-6,42 puppies (P> 0,99...0,999). The maximum index of this indicator of Scanglow genotype was observed at females of 2-year age - 5,48 heads. High-probable positive correlation tie was established between indicators of born and born live puppies (r = 0,36-0,39, p>;0,001).